Heat transfer in a tube with combined V-winglet and twin counter-twisted tape - Pongjet Promvonge; Sompol Skullong (Case Studies in Thermal Engineering, 2021)
The article aims to study experimentally the enhanced thermal-hydraulic performance in a constant heat-fluxed tube inserted with V-winglet-attached twin counter-twisted tapes. Air was utilized as the test fluid and flowed into the tube in a turbulent flow region, Reynolds number in a range of 5300 to 24,000. In the current study, the twin counter-twisted tape (CTT) device having an identical twist ratio were incorporated with 30° V-shaped rectangular winglets (VW) mounted on the tape edges, (hereafter called “VW-CTT”). There were several winglet parameters included a single relative pitch, PR, a 30° winglet attack angle (α) and four values of the winglet height ratio (BR = b/D). Effects of the winglet parameters on friction loss and thermal characteristics in the form of Nusselt number (Nu) and friction factor (f) including thermo-hydraulic performance were examined. The measured results have been revealed that the VW-CTT can augment considerably f and Nu above the smooth tube alone. Using VW-CTT, the increase in Nu is about 1.56–2.3 times the plain tube whilst that in f is around 2.63–5.76 times, depending on Re and BR. The VW-CTT with BR = 0.09 has the optimal thermal performance at about 1.76 for the same pumping power. Finally, Nu and f correlations for the measured data were determined and had the maximum deviations by ±8.4% each.
Keywords: Heat Transfer Mechanisms; Nanofluid Flow and Heat Transfer; Fluid Dynamics and Turbulent Flows